Is it all going south? Four future scenarios for Antarctica. (11th September 2017) - Liggett, Daniela; Frame, Bob; Gilbert, Neil; Morgan, Fraser
ABSTRACT: The future is uncertain for Antarctica, with many possibilities – some more plausible, others more preferable. Indeed, the region and its governance regime may be reaching (or may have reached) a crossroads moment as a result of a series of challenges, including the changing Antarctic climate and environment, increasing human activity, shifting values among Antarctic states and a low-cost, somewhat benign governance regime (the Antarctic Treaty System). Within this context there are a number of interdependent drivers that are likely to influence Antarctica's future over, say, 25 years: global environmental and socio-economic developments; Antarctic governance; Antarctic research, including national Antarctic programme operations; and Antarctic tourism. The research presented here involved a thorough examination of Antarctic literature on current Antarctic developments and challenges, and an assessment of global trends. Scenarios were developed through a facilitated workshop process. From these, four future scenarios were developed based on interactions between these drivers. The resulting scenarios provide a dynamic, evolving possibility space to be explored as a means of understanding where Antarctic issues might evolve, depending on the growth or diminishing importance of drivers. In turn these suggest that more structured polar futures are needed based on formal quantitative and qualitative data.